Age-related hearing loss in older adults: etiology and rehabilitation strategies - Zheng, Qinzhi; Xu, Zhuo; Li, Nan; Wang, Yueying; Zhang, Ting; Jing, Jiapeng (Frontiers in Neuroscience, 2024)
Age-related hearing loss (ARHL) is a prevalent sensory organ disorder among elderly individuals that significantly impacts their cognitive function, psychological well-being, and ability to perform activities of daily living. As the population ages, the number of ARHL patients is increasing. However, the Audiological rehabilitation (AR) status of patients is not promising. In recent years, there has been an increasing focus on the health and rehabilitation of elderly individuals, and significant progress has been made in researching various age-related disorders. However, a unified definition of ARHL in terms of etiology and rehabilitation treatment is still lacking. This study aims to provide a reference for future research on ARHL and the development of AR strategies by reviewing the classification, etiology, and rehabilitation of ARHL.